The causes of bullying: results from the National Survey of School Health (PeNSE) - Wanderlei Abadio de Oliveira; Marta Angélica Iossi Silva; Flávia Carvalho Malta de Mello; Denise Lopes Porto; Andréa Cristina Mariano Yoshinaga; Deborah Carvalho Malta (Universidade de São Paulo, 2015)
Objective: to identify the characteristics and reasons reported by Brazilian students for school bullying. Method: this cross-sectional study uses data from an epidemiological survey (National Survey of School Health) conducted in 2012. A total of 109,104 9th grade students from private and public schools participated. Data were collected through a self-applied questionnaire and the analysis was performed using SPSS, version 20, Complex Samples Module. Results: the prevalence of bullying was 7.2%, most frequently affecting Afro-descendant or indigenous younger boys, whose mothers were characterized by low levels of education. In regard to the reasons/causes of bullying, 51.2% did not specify; the second highest frequency of victimization was related to body appearance (18.6%); followed by facial appearance (16.2%); race/color (6.8%); sexual orientation 2.9%; religion 2.5%; and region of origin 1.7%. The results are similar to those found in other sociocultural contexts. Conclusion: the problem belongs to the health field because it gathers aspects that determine the students' health-disease-care continuum.